PENGARUH CONTENT MARKETING, KREDIBILITAS INFLUENCER, DAN ONLINE CUSTOMER REVIEW TERHADAP NIAT BELI PRODUK LOZY HIJAB DI APLIKASI TIKTOK SHOP - Alia Cahya Amala; William Widjaja (Jurnal Nusa Manajemen, 2026)
The purpose of this study is to evaluate the impact of research variables such as content marketing, influencer credibility, and online customer reviews on consumers' purchase intention of the Lozy hijab brand within the TikTok Shop ecosystem. This research was initiated due to the phenomenon of uneven fluctuations in purchase intentions across various dimensions, which calls for a more consistent digital marketing strategy. By adopting a quantitative methodology, this study applies a non-probability sampling technique using purposive sampling. The sample size determination refers to the theory of Hair et al., (2019) using a 5:1 ratio against 36 research indicators, resulting in a total of 180 participants. Data collection was done by distributing questionnaires to TikTok users who meet the specific research criteria. The empirical findings confirm that all independent variables contribute positively and significantly to triggering the dependent variable, which is purchase intention. Further analysis highlights that influencer credibility is the strongest determinant affecting the purchase intention of Lozy hijab products. Visual appeal and competence in message articulation have proven to be effective tools to convert audience attention into purchase intention. Based on these conclusions, this study is expected to serve as a strategic reference for Lozy hijab management to optimize future promotions. The company is recommended to curate collaborations with influencers who can authentically represent aspirational values, to ensure alignment between the lifestyle portrayed and market preferences.